Teores foliares de nutrientes, índice relativo de clorofila e teores de nitrato e de potássio na seiva do pecíolo na videira 'Niagara Rosada - Tecchio, Marco Antonio; Moura, Mara Fernandes; Paioli-Pires, Erasmo Jose; Terra, Maurilo Monteiro; Junqueira Teixeira, Luiz Antonio; Smarsi, Ronny Clayton [UNESP] (Soc Brasileira Fruticultura, 2011)
A nutritional survey was carried out in 93 vineyards of the wine regions of Jundiai, Sao Miguel Arcanjo and Jales (state of São Paulo-Brazil), aiming to compare the nutrient concentration in leaf samples, the concentration of nitrate and potassium in the petiole sap and the relative chlorophyll index (IRC) of 'Niagara Rosada' vineyard. Leaves, blade and petiole in full bloom vines were sampled in 20 plants selected from each vineyard, and evaluations of the IRC in the leaf blade and the levels of NO3-and K in the petioles sap were realized. Macro and micronutrients concentrations were measured in leaf samples. The sampled vineyards were grouped by region of study, and each vineyard was considered as a replicate sample, totaling 45, 24 and 24 repetitions, in Jundiai, Sao Miguel Arcanjo and Jales, respectively. Sampled vineyards from the Jales region showed higher leaf concentrations of P, K, Ca, Mg, S, Fe and Mn, and also higher IRC and levels of nitrate and potassium in the petiole. These differences were related to the different rootstocks used, which were 'IAC 766', 'IAC 572' and 'Riparia of Traviu', respectively, for Jundiai, Jales and Sao Miguel Arcanjo. The differences highlight the need to adjust the concentration ranges of nutrients in leaf analysis, through regional trials, taking into account the rootstock and the region under study.
Nutrients levels, relative chlorophyll index and concentration of nitrate and potassium in the petiole of 'Niagara Rosada' grapevine
Keywords: Vitis; foliar analysis; mineral nutrition; grapevine